Levels of Breast Milk MicroRNAs and Other Non-Coding RNAs Are Impacted by Milk Maturity and Maternal Diet - Hicks, Steven D.; Confair, Alexandra; Warren, Kaitlyn; Chandran, Desirae (Frontiers in Immunology, 2022)
There is emerging evidence that non-coding RNAs (ncRNAs) within maternal breast milk (MBM) impart unique immunologic effects on developing infants. Most studies examining ncRNAs in MBM have focused on microRNAs. It remains unclear whether microRNA levels are related to other ncRNAs, or whether they are impacted by maternal characteristics. This longitudinal cohort study examined 503 MBM samples from 192 mothers to: 1) identify the most abundant ncRNAs in MBM; 2) examine the impact of milk maturity on ncRNAs; and 3) determine whether maternal characteristics affect ncRNAs. MBM was collected at 0, 1, and 4 months post-delivery. High throughput sequencing quantified ncRNAs within the lipid fraction. There were 3069 ncRNAs and 238 microRNAs with consistent MBM presence (≥10 reads in ≥10% samples). Levels of 17 ncRNAs and 11 microRNAs accounted for 80% of the total RNA content. Most abundant microRNAs displayed relationships ([R]>0.2, adj p< 0.05) with abundant ncRNAs. A large proportion of ncRNAs (1269/3069; 41%) and microRNAs (206/238; 86%) were affected by MBM maturity. The majority of microRNAs (111/206; 54%) increased from 0-4 months. Few ncRNAs and microRNAs were affected (adj p < 0.05) by maternal age, race, parity, body mass index, gestational diabetes, or collection time. However, nearly half of abundant microRNAs (4/11) were impacted by diet. To our knowledge this is the largest study of MBM ncRNAs, and the first to demonstrate a relationship between MBM microRNAs and maternal diet. Such knowledge could guide nutritional interventions aimed at optimizing metabolic and immunologic microRNA profiles within MBM.